Increased Risk of Pregnancy Complications After Stroke: The FUTURE Study (Follow-Up of Transient Ischemic Attack and Stroke Patients and Unelucidated Risk Factor Evaluation). Issue 4 (April 2018) - van Alebeek, Mayte E.; de Vrijer, Myrthe; Arntz, Renate M.; Maaijwee, Noortje A.M.M.; Synhaeve, Nathalie E.; Schoonderwaldt, Hennie; van der Vlugt, Maureen J.; van Dijk, Ewoud J.; de Heus, Roel; Rutten-Jacobs, Loes C.A.; de Leeuw, Frank-Erik
Abstract : Background and Purpose—: The study goal was to investigate the prevalence of pregnancy complications and pregnancy loss in women before, during, and after young ischemic stroke/transient ischemic attack. Methods—: In the FUTURE study (Follow-Up of Transient Ischemic Attack and Stroke Patients and Unelucidated Risk Factor Evaluation), a prospective young stroke study, we assessed the occurrence of pregnancy, miscarriages, and pregnancy complications in 223 women aged 18 to 50 years with a first-ever ischemic stroke/transient ischemic attack. Pregnancy complications (gestational hypertension, diabetes mellitus, preeclampsia, and hemolysis, elevated liver enzymes, low platelet count syndrome) were assessed before, during, and after stroke using standardized questionnaires. Primary outcome was occurrence of pregnancy complications and the rate of pregnancy loss compared with the Dutch population. Secondary outcome was the risk of recurrent vascular events after stroke, stratified by a history of hypertensive disorder in pregnancy. Results—: Data were available for 213 patients. Mean age at event was 39.6 years (SD=7.8) and mean follow-up 9.5 years (SD=8.5). Miscarriages occurred in 35.2% and fetal death in 6.2% versus 13.5% and 0.9% in the Dutch population, respectively ( P <0.05). In nulliparous women after stroke (n=22), in comparison with Dutch population, there was a high prevalence of hypertensive disorders in pregnancy (33.3 versus 12.2%; P <0.05), hemolysis, elevated liver enzymes, low platelet count syndrome (9.5 versus 0.5%; P <0.05), and early preterm delivery <32 weeks (9.0 versus 1.4%; P <0.05). In primi/multiparous women (n=141) after stroke, 29 events occurred (20-year cumulative risk 35.2%; 95% confidence interval, 21.3–49.0), none during subsequent pregnancies, and a history of a hypertensive disorder in pregnancy did not modify this risk (log-rank P =0.62). Conclusions—: When compared with the general population, women with young stroke show higher rates of pregnancy loss throughout their lives. Also, after stroke, nulliparous women more frequently experienced serious pregnancy complications.